Variation in size and shape sexual dimorphism in the Sceloporus scalaris species group (Squamata: Phrynosomatidae) from the Transvolcanic Belt of Mexico. (3rd January 2022) - Cruz-Elizalde, Raciel; Ramírez-Bautista, Aurelio; Lozano, Abraham; Velasco, Julián A; Octavio-Aguilar, Pablo; Berriozabal-Islas, Christian
Abstract: We attempted to identify the factors influencing size and shape dimorphism between sexes, as well as among populations and species in the Sceloporus scalaris group ( Sceloporus aeneus, S. scalaris, S. bicanthalis and S. subniger ). Our analysis focused on five morphological characteristics: snout–vent length, head length, head width, forearm length and tibia length. The effect of environmental variables (precipitation and temperature) on these variables was also tested. We found differences in morphological traits between sexes, and among populations of the same species. The oviparous species ( S. aeneus and S. scalaris ) were larger in overall body size than the viviparous species ( S. bicanthalis and S. subniger ). Differences in overall body size among populations were recorded only in S. aeneus and S. scalaris . Male-biased sexual size dimorphism occurred in oviparous but not viviparous lizards (except for one population of S. bicanthalis ). An absence of sexual size dimorphism was also recorded in S. subniger and some populations of the remaining species. Two different shape patterns were found; the first was female-biased with larger relative body length in almost all populations, which could be explained by fecundity, and the second was male-biased with relatively larger head and limbs in a few populations, which may be explained by sexual selection. The patterns of sexual size and shape dimorphism show that environment, rather than phylogeny, may be determining the extent of sexual dimorphism. These types of studies show the importance of an integrated evaluation of interpopulation and interspecies variation to determine the factors that generate sexual dimorphism.